Pengaruh Model Pembelajaran Discovery Learning Berbasis Tri Kaya Parisudha Terhadap Literasi Sains dan Hasil Belajar IPA Pada Siswa SMP - Kadek Leni Widiartini; Putu Artawan; I Nyoman Tika (Jurnal Penelitian Pendidikan IPA, 2025)
Learning model is a strategy or planning used as a reference in the implementation of the teaching and learning process. One relevant model is Discovery Learning. This study aims to examine the differences in: scientific literacy and science learning outcomes simultaneously, scientific literacy skills, and science learning outcomes between students taught using the Discovery Learning model and those taught using the Tri Kaya Parisudha-based Discovery Learning model. The research employed a quantitative approach with a quasi-experimental method and a Nonequivalent Pretest-Posttest Control Group Design. The subjects were seventh-grade students at SMP Negeri 3 Selemadeg Timur, divided into experimental and control groups. Data collection instruments included a questionnaire to assess scientific literacy and objective tests (pretest and posttest) to measure science learning outcomes. Data were analyzed using MANCOVA. The findings revealed significant differences (p < 0.05) between the two groups in all three aspects examined: simultaneous scientific literacy and learning outcomes, scientific literacy alone, and science learning outcomes alone. These results indicate that the Tri Kaya Parisudha-based Discovery Learning model is more effective in enhancing students' scientific literacy and science learning outcomes.